INNOVATIVE WORK BEHAVIOR IN THE MALAYSIAN MANUFACTURING COMPANY: WHAT REALLY MATTERS? - Ummi Naiemah Saraih; Hanim Hamdan; Tiffany Tijang Sim; Junaid Ansari; Mohd Hazmuni Saidin; Nur Syafiqah A. Rahim (Journal of Human Development and Communication (JoHDeC), 2025)
Employees’ innovative work behaviors (IWB) are essential for the organization as a whole to achieve high development and a competitive advantage in the market. Every firm must develop its system for boosting its employees’ IWB as part of subsequent planning to attain the goal, particularly through HRM practices. We might have less information about which practices matter or how much they will correlate with IWB, but existing literature proves that they can have a significant impact on employees’ IWB. The current study, therefore, addresses two aspects of HRM: training and development and rewards, to determine which aspect is most helpful in predicting an employee’s IWB. The best HRM practices for boosting IWB should also be identified, along with the theoretical justifications for these methods and the relationship between HRM practices and IWB. We used a questionnaire survey to gather information from 170 employees of a manufacturing company in Penang, Malaysia, in order to analyze this research. The connections between all variables were examined using SPSS. In this study, the means for each variable were also presented. According to this research, a high mean indication with the values of μ=4.74 for rewards, μ=4.36 for training and development, and μ=4.70 for rewards IWB was found. The highest correlation between IWB and training and development was found in the Pearson correlation data (r=.362, p=.000), followed by rewards (r=.767, p=.000). The study’s conclusions can help human resource practitioners design an HRM system that promotes inventive employee behavior and fosters an innovative workplace.